Citizenship Policies in the New Europe Expanded and Updated Edition - Bauböck, Rainer; Perchinig, Bernhard; Sievers, Wiebke (IMISCOE Research, 2009)
The two most recent EU enlargements in May 2004 and in January 2007 have greatly increased the diversity of historic experiences and contemporary conceptions of statehood, nation-building and citizenship within the Union. How did newly formed states determine who would become their citizens? How do countries relate to their large emigrant communities, to ethnic kin minorities in neighbouring countries and to minorities in their own territory? And to which extent have their citizenship policies been affected by new immigration and integration into the European Union? Citizenship Policies in the New Europe describes the citizenship laws in each of the twelve new countries as well as in the accession states Croatia and Turkey and analyses their historical background. Citizenship Policies in the New Europe complements two volumes on Acquisition and Loss of Nationality in the fifteen old Member States published in the same series in 2006. This title is available in the OAPEN Library - http://www.oapen.org.